The relationship between parenting styles and emotional intelligence toward internet addiction among undergraduate students in Universiti Putra Malaysia - Che Sembilan, Che Nur Aainaa; Salim, Siti Suria (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The purpose of this study is to examine the relationship between parenting and emotional intelligence to internet addiction among undergraduates’ students. Quantitative research method and multistage cluster random sampling were used in this study. The research instruments in this study included Parenting Styles Questionnaire by Robinson (1995), Emotional Intelligence Questionnaire by National Health Service and Internet Addiction Test by Kimberly Young.